Operations Research as a Profession - Churchman, C. West (Management Science, 1970)
This paper is concerned with the profession of operations research and specifically with the preparation for the profession. On a fairly general plain, the paper expresses a concern about the future of a profession which ought to be in the lead in the growing societal anxiety over poverty, pollution and privacy, but in fact plays virtually no significant role in these matters. In his autobiography, Memories, Dreams, Reflections, C. G. Jung argues for a fascinating way of telling the story of one's life. There are, he says, two stories. One story is the rational, a story of a man's struggles, frustrations and joys in seeking his life's goals. The other is the “irrational,” the primitive often unexpressed mythic elements of his life. At some risk of perverting the richness of Jung's suggestion, I'd like to tell two stories of a profession, operations research, but in the end I'll not be sure which is the rational. The reason for telling these two stories is to obtain a critical overview of the profession of operations research, primarily to assess its educational base, not just in colleges and universities, but in the overall program of learning: in meetings, journals and informal discussions.